Assessment of energy and exergy efficiencies of mini photovoltaic modules - Yildiz, Ahmet; Cakmak, Gulsah; Bilgic, Yusuf (Inderscience Enterprises Ltd, 2024)
In this study, the electrical performance of the 2.4 W mini photovoltaic module was determined under different solar radiation conditions in June 2022. A comprehensive thermodynamic analysis was performed, involving the calculation of energy and exergy efficiency based on data from day-long experimental studies. Efficiency values obtained by considering the measured solar irradiance intensity were observed. Energy efficiency and exergy efficiency ranged from 17% to 19% and 6% to 11%, respectively. It has been observed that the exergy efficiency increases with the intensity of solar radiation and the ambient temperature has a significant contribution to this case.
Keywords: exergy; energy; power; efficiency; mini photovoltaic